2019
DOI: 10.1186/s12884-019-2574-2
|View full text |Cite
|
Sign up to set email alerts
|

Provider advice on physical activity and nutrition in twin pregnancies: a cross-sectional electronic survey

Abstract: Background: Health care providers should counsel pregnant patients on physical activity and nutrition to improve pregnancy outcomes. However, little is known about provider advice on these lifestyle behaviors among women pregnant with twins, a growing population at high risk for pregnancy complications. We examined the prevalence and content of provider advice on physical activity and nutrition among women pregnant with twins. Methods: A cross-sectional electronic survey was administered to 276 women who deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
(44 reference statements)
1
16
1
Order By: Relevance
“…These ndings suggest that physicians are promoting PA to patients who may bene t most from the recommendation [37,51].Conversely, in Brazil, patients reported having leisure-time PA were more likely to receive PA advice [52,53]. Similarly, patients with higher PA levels tend to initiate more conversations with their providers about PA compared to those with poorer lifestyle habits [54].…”
Section: Discussionmentioning
confidence: 88%
“…These ndings suggest that physicians are promoting PA to patients who may bene t most from the recommendation [37,51].Conversely, in Brazil, patients reported having leisure-time PA were more likely to receive PA advice [52,53]. Similarly, patients with higher PA levels tend to initiate more conversations with their providers about PA compared to those with poorer lifestyle habits [54].…”
Section: Discussionmentioning
confidence: 88%
“…In our study 51% of the respondents claimed to have contraindications to exercises determined by a health care provider. According to Whitaker et al, 42% of pregnant women in the USA were recommended to restrict their activity levels with additional 13% being prescribed bed rest [11]. Bed rest is commonly advised to prevent preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Twin birth rate is on the rise. Increasing trends in twin birth rates have been observed worldwide; in the USA, the rate of twin deliveries has increased by almost 80% since the 1980s and in Poland an increase of 27% of multiple birth rate has been observed since 1997 [9][10][11]. In 2018 a total of 3% of all births were multiple in Poland [12].…”
Section: Introductionmentioning
confidence: 99%
“…Women were eligible for the study if they met the following self-reported criteria: aged 18–44 years, twin birth within the last three years, first prenatal visit prior to 16 weeks gestation, received prenatal care in the United States, knowledge of twin gestation before the third trimester, and not currently pregnant. Women who met eligibility criteria were invited to complete a cross-sectional internet-based survey assessing health behaviors as well as health care provider advice on weight gain, physical activity, and diet during their twin pregnancy (see Supplementary File 1 for study survey) [ 24 ]. This paper reports findings related to GWG.…”
Section: Methodsmentioning
confidence: 99%